Data mining for detecting signals of adverse drug reaction of doxycycline using the Korea adverse event reporting system database. (19th May 2022) - Heo, Jae Young; Cho, Moon Kyun; Kim, Sooyoung
Abstract: Background: Doxycycline is one of the most prescribed antibiotics by dermatologists. However, the concern regarding adverse events of doxycyline has been rising. Objective: To detect the adverse events of doxycycline using the Korea Adverse Events Reporting System (KAERS) database from January 2014 to December 2018 through a data mining method. Methods: A signal was defined as one satisfying all three indices; a proportional reporting ratio, a reporting odds ratio, and an information component. We further checked whether the detected signals exist in drug labels in Korea and five developed countries, the United States, the United Kingdom, Germany, Canada, and Japan. Results: A total of 3, 365, 186 adverse event-drug pairs were reported and of which 3, 075 were associated with doxycycline. Among the thirty-seven signals, nineteen (malaise, ileus, confusion, malignant neoplasm, ectopic pregnancy, ovarian hyperstimulation, vaginal hemorrhage, bone necrosis, acne, rosacea, seborrheic dermatitis, folliculitis, skin ulceration, crusting, dry skin, paronychia, mottled skin, application site reaction, and application site edema) were not included on any of the drug labels of the six countries. Conclusion: We identified nineteen new doxycycline signals that did not appear on drug labels in six countries. Further studies are warranted to evaluate the causality of the adverse events with doxycycline.